Desarrollo turístico para la parroquia Las Nieves, cantón Nabón, provincia del Azuay - Guaman Morocho, Alexandra Elizabeth Guaman Morocho (2024)
Tourism development is the planning, promotion and management of destinations to balance tourist satisfaction with the conservation of the natural and cultural environment, and the economic and social well-being of host communities. With the aim of supporting the tourism development of the sector, this research has been proposed, the general objective which is: Develop a tourism development proposal for the Parish, which is based on two specific objectives: Diagnose the current tourism system and propose tourism strategies for “Las Nieves Parish”. In the methodology, the methodological guide for the preparation of cantonal tourism development plans was used. It was proposed by the (Association of Municipalities of Ecuador (AME) for the first objective 2 and 3 plus the Manual for local tourism diagnosis by Carla Ricaurte, and in the second objective the phases 4 and 5. The techniques used, were the survey, bibliographic review and the Método de Análisis Rápido y Planificación Participativa (MARPP) technique, resulting in the Parish having 23 attractions and 2 tourist resources, in which the craft workshops and its gastronomy stand out. Despite the lack of a tourist plans and people who are specialized in tourism, the territory allows taking advantage of current tourist trends towards rural, community, gastronomic and agritourism tourism, to promote tourist activity and the visit of both national and international tourists. After diagnosing the tourist potential of the territory, it was possible to establish strategies to take advantage of it, which include the proposal of a tourist route, the need to have signals of the tourist attractions, the implementation of permanent activities there and having a tourist brand by which the Parish should be known, promoting local development for the population.